COMMUNITY UNIVERSITIES AND NATIONAL ECONOMIC DEVELOPMENT - Machado dos Santos, Adelcio; Sprandel da Silva, Solange (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes the role of community universities in national economic development, emphasizing their territorial presence, outreach activities, scientific production, and contributions to strengthening regional capacities. Community universities are defined as non-state public institutions, non-profit in nature, committed to providing quality higher education and promoting social transformation in the territories where they operate. Based on a literature review and analysis of secondary data, the study demonstrates that these institutions significantly impact regional educational and socioeconomic indicators, acting as vectors of endogenous and sustainable development. However, the community university model still lacks institutional recognition and specific public funding policies. It is concluded that strengthening community universities is strategic for promoting a more equitable educational policy and for building an inclusive national development project.